Homocysteine Levels Are Associated With the Rupture of Intracranial Aneurysms - Wei, Sen; Yuan, Xin; Li, Dongdong; Guo, Xinbin; Guan, Sheng; Xu, Yuming (Frontiers in Neuroscience, 2022)
Background: Homocysteine (Hcy) levels may be associated with the development of intracranial aneurysms (IAs). However, whether it increases the risk of rupture of IAs is unknown. This study aimed to determine the association between homocysteine levels and IA rupture. Methods: We retrospectively reviewed patients with IAs and subarachnoid hemorrhage (SAH) at our hospital between January 2019 and May 2021. Clinical data, including Hcy levels and IA images, were assessed. The association between Hcy level and IA rupture was investigated using multivariate logistic regression analyses in patients with IAs and SAH. Results: A total of 589 patients were included. 546 patients with IAs, including 331 UIA (Unruptured IA) and 215 RIA (Ruptured IA). The average age was 57.43±10.86 years old, and 67.03% were women. Among them, all 215 RIAs lead to SAH. In addition, we also enrolled 43 non-aneurysmal subarachnoid hemorrhage (Na-SAH) patients. The average age was 54.12±10.55 years old, and 53.48% were female. After adjusting for confounders in the multivariate model, Hcy levels were correlated with the rupture of IA (odds ratio [OR] 1.069; 95% confidence interval [CI] 1.025–1.114, p = 0.002) and a-SAH (OR 1.083; 95% CI 1.002–1.170, p = 0.046). Conclusions: Hcy levels were associated with IA rupture. These findings provide novel insights into IAs rupture, and future studies are needed to confirm this relationship.